Growth Trajectories in Stimulant-Treated Children Ages 6 to 12: An Electronic Medical Record Analysis. Issue 2 (February 2023) - Biederman, Joseph; DiSalvo, Maura; Green, Allison; Hutt Vater, Chloe; Driscoll, Haley; Faraone, Stephen V.
Abstract : This article has supplementary material on the web site: www.jdbp.org . ABSTRACT: Objective: The aim of this study was to evaluate growth trajectories in stimulant-exposed and stimulant-unexposed children using electronic medical record data from a large health care organization attending to moderating effects of the magnitude of exposure to stimulants, sex, and race. Methods: Weight, height, body mass index (BMI), prescription, and sociodemographic information were extracted from the electronic medical records of a large health care organization. Included were children who were 6 to 12 years at the time they were receiving stimulants with a concurrent growth assessment (index assessment) plus 1 to 4 years of additional growth assessments thereafter. Non–attention-deficit/hyperactivity disorder (ADHD) children who were unexposed to stimulants were age and sex matched to those exposed. Stimulant exposure was examined as the total number of months with stimulant prescriptions, percentage of follow-up time exposed to stimulants, and cumulative stimulant dose. Results: Our sample consisted of 323 children exposed to stimulants with available growth data and 1615 unexposed children. Small but significant decreases in height trajectories were found over time in exposed children compared with those unexposed. Weight and BMI trajectories decreased in the first year of follow-up with stabilization and increased thereafter. Growth trajectory effects were largest in girls (height, weight, and BMI), White children (weight), and children with more total stimulant exposure (weight). Conclusion: This comprehensive analysis of an ecologically informative sample attending to key covariates of the magnitude of exposure to stimulants, sex, and race extends previous findings, showing that effects on growth trajectories are small and do not appear to pose a significant clinical concern for most children with ADHD treated with stimulants from childhood onto adolescent years.